Factors Influencing the Health Service Center Application for Hypertension Patients in Humbang Hasundutan Regency - Rifka Banjarnahor; Lita Sri Andayani; Destanul Aulia (RIRAI Publisher, 2023)
Based on data from the Humbang Hasundutan Regency Health Office in 2019 there were 53,004 cases of hypertension and of the total sufferers only 33 percent used health services. This study aims to analyze the factors that influence the utilization of health services at Public Health Center for hypertension sufferers in Humbang Hasundutan Regency. This research is a quantitative analytic survey research with a cross sectional design. The sample used was 110 people with the sampling technique using accidental sampling. Data analysis used univariate and bivariate analysis. The results showed that the related variables were Knowledge (p=0.005), Ownership of Health Insurance (p=0.001) and Need for Services (p=0.001) with Utilization of Health Services at Health Centers for Hypertension Patients in Humbang Hasundutan Regency. Suggestions for this study are that health workers are expected to be able to go into the field or to the community directly to conduct counseling and outreach to the community that is more intensive regarding information about non-communicable diseases (PTM), especially in this case hypertension, so that people know more about disease prevention and control hypertension. So that people have more good knowledge to improve public health status. Public Health Center is expected to become a health facility that can help and improve health services both in terms of providing services to people with hypertension and in terms of infrastructure and drug availability, so that people can more easily understand the flow and procedures for utilizing health services.